Federal Revenue Sharing, Marginalisation and Sub-National Inter-Regional Inequality in Human Capital Development in South-Eastern and Southern Nigeria - Ingwe, Richard; Ukwayi, Joseph K.; Utam, Edward U. (Quaestiones Geographicae, 2013)
Regional development planning/management responds to needs for preventing inequality among regions within nations characterised by multi-culturality and variation among regions, through the planning/management of appropriate programmes and policies. This paper examines inequality in the development of two of Nigeria’s states in the geographical South-East and the political South-South. Among other issues, historical conflicts among various ethno-cultural groups constituting Nigeria and culminating in violence (e.g. the 1967-1970 civil war fought against the programme of Ibo (a socio-cultural group) seceding from Nigeria’s federation to found Biafra) are reviewed. Despite Nigeria’s tragic civil war, inequality persists. We examine inequality resulting from systematic implementation of policies/programmes of Nigeria’s federal government institutions that marginalise Cross River State. Using the methods of comparative analysis and a descriptive case study, we show the consequences of marginalisation policies implemented by the federal government alone or in collaboration with (i.e. in support of) Akwa Ibom State for the development of human capital in Cross River State. The specific acts of marginalisation referred to here include: the ceding of the Bakassi Peninsula - a part of Cross River State - to the Republic of Cameroon in 2005, and more recently (2009) another ceding of 76 oil wells, hitherto the property of Cross River State, to Akwa Ibom State. We argue that, strengthened by marginalising/polarising policies (higher revenue allocation based on derivation principle of oil production), Akwa Ibom’s ongoing implementation of free education policy promises to facilitate its achievement of millennium development goals in basic education by 2015, beyond which it might reach disproportionately higher levels of tertiary educational attainment by 2024 and after. By contrast, the contrived dwindling of oil revenue accruing to Cross River State deprives it of funding for competitive human capital development programme(s). We recommend that Cross River State employs serious monitoring of marginalising schemes against its people considering recent traumatising experience, and plan/implement human capital development programmes aimed to improve its competitiveness under the context of intra-regional inequality.